Epidural abscess after combined spinal-epidural block - Schröter, Jens; Djamba, wa Djamba; Hoffmann, Volker; Bach, Alfons; Motsch, Johann (Canadian journal of anesthesia, 1997)
We report the first case of abscess formation after combined spinal-epidural block (CSE). Penetation of the dura in CSE may constitute an addtional risk of subarachnoid spread of bacteria when post-puncture epidural infection is present.
Gesehen am 21.11.2023